2014
DOI: 10.1186/s13058-014-0430-x
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming endocrine resistance due to reduced PTEN levels in estrogen receptor-positive breast cancer by co-targeting mammalian target of rapamycin, protein kinase B, or mitogen-activated protein kinase kinase

Abstract: IntroductionActivation of the phosphatidylinositol 3-kinase (PI3K) pathway in estrogen receptor α (ER)-positive breast cancer is associated with reduced ER expression and activity, luminal B subtype, and poor outcome. Phosphatase and tensin homolog (PTEN), a negative regulator of this pathway, is typically lost in ER-negative breast cancer. We set out to clarify the role of reduced PTEN levels in endocrine resistance, and to explore the combination of newly developed PI3K downstream kinase inhibitors to overco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 59 publications
1
44
0
Order By: Relevance
“…In this study, we showed that FOXA1 overexpression in ER (4,5,8,37). We report here that increased levels of FOXA1 coordinate at least partly with ER in this transcriptional reprogramming, leading to perturbed gene signatures and signaling pathways associated with endocrine resistance.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In this study, we showed that FOXA1 overexpression in ER (4,5,8,37). We report here that increased levels of FOXA1 coordinate at least partly with ER in this transcriptional reprogramming, leading to perturbed gene signatures and signaling pathways associated with endocrine resistance.…”
Section: Discussionmentioning
confidence: 54%
“…Although there are many causes for resistance, the most predominant mechanisms include altered ER signaling and interactions between ER, its coregulators, and various growth factor pathways. These alterations facilitate adaptation from ligand-dependent to ligand-independent ER activation, which is further triggered by cross-talk with growth factor receptor (GFR) signaling pathways (3)(4)(5)(6). However, the key mediators of ER transcriptional reprogramming in promoting endocrineresistant (Endo-R) breast cancer remain poorly understood.…”
mentioning
confidence: 99%
“…Upregulation of alternative signalling pathways is a third mechanism leading to endocrine resistance, and the role of the PI3K/AKT/mTOR pathway in this context has been heavily investigated. [32][33][34][35][36][37] Increased AKT activity was first recognized as a feature of aggressive cancer, and associated with endocrine resistance in breast cancer, where, in fact, AKT and PI3K can mediate growth signalling via ERα in the absence of oestrogen. 32,33 Activating mutations in PIK3CA, the gene encoding the catalytic subunit of PI3K, are common in breast cancer, being present in 45% of luminal A and 29% of luminal B tumours.…”
Section: Mechanisms Of Endocrine Resistancementioning
confidence: 99%
“…Hormone receptor status may also be used as biomarkers for targeted therapies. Recently, studies evaluating the prognosis of breast cancer patients suggest that PIK3CA mutations are significantly associated with ER/PR expression [23] and that PTEN, a negative regulator of this pathway, is typically lost in ER-negative breast cancer [24]. Herein we show molecular alteration that leads to enhanced PI3K pathway signaling in HR+ USC, and propose that inhibition of PI3K/AKT pathway may overcome endocrine resistance in the subset of HR negative patients.…”
Section: Discussionmentioning
confidence: 63%